ANALISIS YURIDIS PENERAPAN TINDAK PIDANA PROSTITUSI ONLINE MELALUI MEDIA SOSIAL (Studi Kasus Putusan Nomor : 177/Pid.B/2020/PN.Cbn) - Baria, B; Ramadhani, Rizki; Tamrin, Husni (Bahasa Indonesia, 2022)
Prostitution through social media is now under the scrutiny of society, the law apparatus is widespread and serious. The impacts that occur on social media prostitution are not only related to one or two aspects, but are related to social problems in society between one another. This research discusses issues regarding judicial analysis in the application of law to perpetrators of criminal acts through social media in case 177/Pid.B/2020/PN.Cbn whether the application and enforcement of the law are appropriate. The normative writing method uses research methods on secondary data. From the results of the study it can be concluded that the application of law in imposing criminal sanctions on perpetrators of prostitution through social media is inappropriate because judges do not apply the principle of lex specialist derogate lex generalis.